2019
DOI: 10.3906/bot-1704-40
|View full text |Cite
|
Sign up to set email alerts
|

Determination of trophic weight and indicator values of diatoms in Turkish running waters for water quality assessment

Abstract: This study, the first such attempt in Turkey, aimed to investigate the distribution of diatom species related to the variation of total phosphorus (TP) in eight basins to determine trophic weight and indicator values of diatom species and to develop the Trophic Index-Turkey (TIT) for assessing the ecological status of freshwaters. The distribution of the diatom species in 225 running water bodies from 8 basins of Turkey was determined in 2014 (summer and fall) and 2015 (spring and summer) in association with T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 22 publications
2
38
0
1
Order By: Relevance
“…The TIT (Trophic Index of Turkey) was developed specifically for Turkish rivers [55]. In the present work the TIT index was also calculated, and since there were no significant correlations with environmental parameters and the TIT, it is thought that the index did not work in the watercourses of the Sakarya River basin.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The TIT (Trophic Index of Turkey) was developed specifically for Turkish rivers [55]. In the present work the TIT index was also calculated, and since there were no significant correlations with environmental parameters and the TIT, it is thought that the index did not work in the watercourses of the Sakarya River basin.…”
Section: Discussionmentioning
confidence: 89%
“…All the indices were transformed in Omnidia software to range from 0 (or 1) to 20 to be comparable (Table 2). Additionally, the Trophic Index of Turkey (TIT) was calculated for checking its applicability for assessment water quality of studied waters [55]. Table 1.…”
Section: Field and Laboratory Studiesmentioning
confidence: 99%
“…This study suggested that diatom metrics can be effectively used for running water quality assessment. Development of ecoregionally specific diatom metrics is warranted since climate, geology, anthropogenic activities, and land use may affect the preferences of diatom assemblages and their trophic weight (Gomá et al, 2004;Lobo et al, 2004;Soininen, 2007;Çelekli et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…After the determination of the reference areas, biological, hydromorphological and physico-chemical quality variables of sampling stations and their typologically related reference areas have to be measured for the bioassessment of ecosystems (Moldoveanu et al, 2017;Charles et al, 2021). And then the Ecological Quality Ratio (EQR) of surface waters can be calculated based on the comparison of the measured metric (observed) in the water bodies with expected metric value in the specific reference area (e.g., EC, 2009;Hering et al, 2010;Lazaridou et al, 2018;Çelekli et al, 2019b). Thus, EQR outcomes as observed/expected metric values.…”
Section: European Water Framework Directivementioning
confidence: 99%
“…Bioindicators in the aquatic ecosystem give crucial responses to pollution gradient, which can provide valuable information about health and the overall ecological status of environments (Rott et al, 1999;Kelly et al, 2008;Birk et al, 2012;Toudjani et al, 2017;Çelekli et al, 2019b). Concerning that, tolerances and sensitivities of bioindicator species have been used to investigate and assess the potential effects of environmental pollutants on living things (Rott et al, 1999;Kelly et al, 2008;Çelekli et al, 2019b;Cozea et al, 2020). The advantage of using bioindicators is the integration of these organisms in the evaluated habitats (Lobo et al, 2016;Cozea et al, 2020).…”
Section: Diatom Assemblages As Bioindicatormentioning
confidence: 99%